Developing CakeApp-Based Infographics to Support Teaching Speaking in Tourism Vocational High Schools - I Wayan Gunawan; I G A Lokita Purnamika Utami; Dewa Ayu Eka Agustini (Journal of Educational Study, 2026)
The integration of digital learning tools has become increasingly important in English as a Foreign Language (EFL) instruction, particularly in vocational high schools where students are required to develop workplace communication skills. Previous studies have reported the effectiveness of mobile applications in supporting language learning; however, limited attention has been given to providing practical pedagogical guidance that helps teachers integrate such applications into speaking instruction, especially in tourism vocational contexts. As a result, many English teachers continue to face difficulties in translating digital platforms into structured and meaningful classroom speaking activities. To address this gap, this study aimed to develop CakeApp-based infographics that function as practical teaching speaking ideas for tenth-grade English teachers in a tourism vocational high school. The study employed a Design and Development (D&D) research approach using the ADDE model, which consisted of analysis, design, development, and evaluation stages. Data were collected through syllabus analysis, classroom observation, teacher interviews, expert judgment, and user review. The findings indicated that the developed infographics achieved an excellent level of quality in terms of content relevance, instructional clarity, visual design, and practicality. Expert and user evaluations further confirmed that the infographics effectively assist teachers in integrating CakeApp into speaking instruction. Therefore, this study concludes that CakeApp-based infographics can serve as pedagogical guides that support interactive and context-based speaking activities in tourism vocational education.